An investigation of athletes satisfaction towards teammates and its relationship with athletes intrinsic motivation - Abu Samah, Irza Hanie; Omar, Zoharah; Osman, Abdullah (Global Society of Scientific Research and Researchers, 2015)
Satisfaction of an athlete is important to indicate intrinsic motivation. Satisfaction is a feeling that rises from the perception, mind and thinking of and individual. Individual satisfaction upon group or teammates somehow may influence on intrinsic motivation. This study was conducted during the National Open Competition Games (Archery) in Malaysia. 139 questionnaires were administered during the games. Findings shows that the majority of respondents have high level on athlete’s satisfaction on teammates with 75.5% (M=3.99, SD=0.68). Respondents also portray high level of intrinsic motivation whereby the percentage is 82.70%, (M=4.16, SD=0.62). The result of the study indicate that there is a significant relationship on athletes’ satisfaction on teammates towards intrinsic motivation (p<0.01, r= 0.428).